The effect of osteoarthritis exercise on pain and joint range of motion in osteoarthritis patients - Dewi Masyitah; Mashudi Mashudi; Bettywati Eliezer Tumanggor; Yessi Fadriyanti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Aims. Osteoarthritis is a degenerative and progressive disease characterized by abrasion of joint cartilage and irregular formation of new bone on the surface of the joints. Pain becomes the main symptom followed by a decrease in joint range of motion, causing disability and interfering with daily activities. The purpose of this study was to determine the effect of osteoarthritis exercise on pain and joint range of motion in osteoarthritis patients. Methods. The research design used a quasy experiment with a non-equivalent control group design approach. The sample used was 70 respondents for each intervention group and control group. Intervention in the form of physical exercise osteoarthritis exercise guided by an instructor and using audio-visual media. Exercise is carried out 3 times a week for 2 weeks. For stretching and flexibility exercises using yoga mats and bath towels and for strength building exercises using chairs. The pain scale was measured with a numeric rating scale (NRS) instrument and measurement of joint range of motion using a goniometer. Data analysis used numerical comparative analytic paired-sample t test and independent t test. Findings. The results showed that the results of the paired t test (p) <0.05. thus indicating that there is an effect of providing osteoarthritis gymnastics training intervention on reducing the pain scale. The results of the paired t test (p) <0.05. thus indicating that there is an effect of providing osteoarthritis exercise training interventions on the scale of joint range of motion. The results of the independent t test (p) <0.05, meaning that there is a difference in the osteoarthritis pain scale before and after the intervention, while the test for differences in joint range of motion scale shows a non-significant value of p> 0.05. Conclusion. The conclusion of the study was that there was an effect of osteoarthritis gymnastics training in reducing the osteoarthritis pain scale and joint range of motion scale. Then there is no difference between the control group and the intervention group who get gymnastic exercises and do not get osteoarthritis gymnastic exercises.